ENGLISH TEACHERS' PROFESSIONAL DEVELOPMENT IN KABUPATEN KUPANG - -, RISYONO; BERA, LAURENSIUS KIAN; KOLO, CLEMENS (Postgraduate School, Universitas Nusa Cendana, 2023)
This narrative inquiry study aimed to explore teachers’ views of their professional development practices. Qualitative studies are used to truly comprehend through “thick rich” descriptions what's happening (or not) from the standpoint of the English teacher in reference to their professional development practices and related impact on student outcomes. This study involved a purposeful sample of 3 English teachers of Senior High School level in Kabupaten Kupang, acknowledged by the chairperson of the English teacher working group of Senior High Schools in Kabupaten Kupang, (MGMP/Musyawarah Guru Mata Pelajaran Bahasa Inggris SMA Kabupaten Kupang) as “committed” to a life-long love of learning and to applying new knowledge gained from professional development practices into their classrooms. These teachers reflected on the experiences they valued, how they employed their learning to support student-learning outcomes, the types of support they obtained, and the barriers they faced. The findings of this study show that teachers value professional development experiences that improve their teaching skills and offer applicable and practical knowledge. To be successful, teachers believe that they need more time to continue informal dialogue with colleagues while applying new learning. Additionally, to support colleagues, teachers benefit from the further assistance provided by internal coaches. Teachers experience barriers related to lack of time and sense of ownership, preconceived opinions, inadequate training, and management of non-compliant student behaviors. In reference to student outcomes, these teachers mainly used their observational skills rather than formal assessments to evaluate the impact of new teacher learning on student outcomes.